Application of high temperature phase change materials for improved efficiency in waste-to-energy plants - Dal Magro, Fabio (2018)
This study reports the thermal analysis of a novel thermal energy storage based on high temperature phase change material used to improve efficiency in waste-to-energy plants. Current waste-to-energy plants efficiency is limited by the steam generation cycle which is carried out with boilers composed by water-walls (i.e. radiant evaporators), evaporators, economizers and superheaters. Although being well established this technology is subjected to limitations related with high temperature corrosion and fluctuation in steam production due to the non-homogenous composition of solid waste; this leads to increased maintenance costs and limited plants availability and electrical efficiency. The proposed solution in this paper consists of replacing the typical refractory brick installed in the combustion chamber with a PCM-based refractory brick capable to store a variable heat flux and to release it on demand as a steady heat flux. By means of this technology it is possible to avoid steam production fluctuation, to increase temperature of superheated steam over current corrosion limits (450°C) without using coated superheaters and to increase the electrical efficiency beyond 34%. In the current paper a detailed thermo-mechanical analysis has been carried out in order to compare the performance of the PCM-based refractory brick against the traditional ones. The PCM considered in this paper is aluminium and its alloys whereas its container consists of high density ceramics (such as Al2O3, AlN and Si3N4); the different coefficient of linear thermal expansion for the different materials requires a detailed thermo-mechanical analysis to be carried out to ascertain the feasibility of the proposed technology.